CrimRxiv 2021
DOI: 10.21428/cb6ab371.5f335e6f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Criminal Transactional Methods in Cyberspace as Understood in an International Context

Abstract: McMurdie 2016), due to the quickly-evolving and vast nature of these crimes (Holt 2018), which typically involve more effort and cross-border expense and access difficulties than do most offline crimes in the Pursue mode. Policing has been slow to adjust to the rise of digital crimes and fraud, not least because it often means giving up functions currently performed, which meet resistance (HMICFRS 2019a(HMICFRS , 2019b."Effectiveness" in policing cybercrime needs to be clearly defined and should be seen on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For crypto-asset businesses to operate legally, they are required to register with the FCA. Registration is mandatory for any activities involving the exchange or conversion of cryptocurrencies, encompassing the facilitation of buying, selling and trading these crypto-assets (Gundur et al 2021).…”
Section: Registration and Licensing Requirementsmentioning
confidence: 99%
“…For crypto-asset businesses to operate legally, they are required to register with the FCA. Registration is mandatory for any activities involving the exchange or conversion of cryptocurrencies, encompassing the facilitation of buying, selling and trading these crypto-assets (Gundur et al 2021).…”
Section: Registration and Licensing Requirementsmentioning
confidence: 99%
“…Recently conducted studies have shown that the cyberspace has constantly been under threats since the emergence of the novel virus, as various kinds of cyber spies, thieves, saboteurs, and thrill seekers have found their ways into individual computer systems, thieving personal data and trade secrets, breaking off Web sites, disrupting organizational services, sabotaging data and systems, launching computer viruses and worms, infusing malwares and trojans into the computer devices, conducting fraudulent transactions, as well as scamming individuals and companies [15][16][17]. It was equally observed in the works Abukari, and Bankas [18], that these attacks were aided with exponentially powerful and easy-to-use software tools, which are freely available from millions of Web sites on the Internet.…”
Section: The Social Ills Of Covid-19 On Cyberspacementioning
confidence: 99%
“…In addition, "one of the main reasons ransomware has become prevalent globally is that it uses the Tor system and asks victims to pay in bitcoin or other cryptocurrencies. e Tor system and cryptocurrencies make crime investigation difficult, especially when it comes to tracing the money flow [11]. "…”
Section: General Approachmentioning
confidence: 99%
“…is implies that cybercriminals can acquire their own ransomware, including those with relatively low levels of expertise [11]. For that, well-known exploit kits (EKs) like Rig, Neutrino, and Magnitude are available.…”
Section: Introductionmentioning
confidence: 99%